Maternal Low Volume Circulation Relates to Normotensive and Preeclamptic Fetal Growth Restriction - Gyselaers, Wilfried; Lees, Christoph (Frontiers in Medicine, 2022)
This narrative review summarizes current evidence on the association between maternal low volume circulation and poor fetal growth. Though much work has been devoted to the study of cardiac output and peripheral vascular resistance, a low intravascular volume may explain why high vascular resistance causes hypertension in women with preeclampsia that is associated with fetal growth restriction, and at the same time presents with normotension in fetal growth restriction itself. Normotensive women with small for gestational age babies show normal gestational blood volume expansion superimposed upon a constitutionally low intravascular volume. Early onset preeclampsia (occurring prior to 32 weeks) is commonly associated with fetal growth restriction, and poor plasma volume expandability may already be present before conception, preceding gestational volume expansion. Experimentally induced low plasma volume in rodents predisposes to poor fetal growth and interventions that enhance plasma volume expansion in fetal growth restriction have shown beneficial effects on intrauterine fetal condition, prolongation of gestation and birth weight. This review makes the case for elevating the maternal intravascular volume with physical exercise with or without Nitric Oxide Donors in fetal growth restriction and early onset pre-eclampsia, and evaluating its role as a potential target for prevention and/ or management of these conditions.